Bacterial diversity of stingless bee honey in Yunnan, China: isolation and genome sequencing of a novel acid-resistant Lactobacillus pentosus (SYBC-MI) with probiotic and L. tryptophan producing potential via millet fermentation - Basharat, Samra; Meng, Tiantian; Zhai, Lixin; Hussain, Asif; Aqeel, Sahibzada Muhammad; Khan, Salman; Shah, Obaid Ullah; Liao, Xiangru (Frontiers in Bioengineering and Biotechnology, 2023)
Stingless bee (Hymenoptera, Apidae, and Trigona) honey is a remarkable "miracle liquid" with a wide range of medical benefits for conditions including gastroenteritis, cataracts, and wound healing. Our study aimed to isolate, identify, and characterize acid-resistant Lactobacillus spp. from sour honey distributed in Yunnan, China. To assess the safety of an entirely novel Lactobacillus pentosus strain, S4 (OM618128), based on probiotic property evaluation and whole-genome sequencing analysis. A 16S rRNA gene high-throughput sequencing analysis showed that Lactobacillus was abundant at the genus level in sour honey. Seven Lactobacillus strains (viz. S1-7) were isolated from sour honey using a multiple-anaerobic culture enrichment method. One potential acid-resistant isolate, Lactobacillus sp. S4, was obtained after screening the seven Lactobacillus isolates, and it had the highest lactic acid production (17.62 g/L), followed by Lactobacillus sp. S3 (17.07 g/L). Phylogenetic and comparative analyses of conserved sequence regions have shown that all seven strains are phylogenetically located in the Lactobacillus pentosus sub-cluster. In L. pentosus SYBC-MI, there is a circular chromosome (3288615 bps) and 11,466 bps plasmids. GC content is 44.03%. The number of predicted genes is 3129, with 16 rRNAs and 74 tRNAs present. During the fermentation of foxtail millet by seven Lactobacillus pentosus (S1-7) strains isolated from sour honey, a potential tryptophan accumulating isolate, Lactobacillus pentosus S4, was obtained, which could reach a maximum tryptophan content of 238.43 mgL -1 that is 1.80 times the initial tryptophan content in the fermentation broth. This strain has strong acid tolerance, salt tolerance, and fermentation acid production abilities. This strain degrades nitrite at a rate of over 99%, and it has high probiotic potential as well. This project has established a solid foundation for further exploring the excellent lactic acid bacteria in sour honey. It is also investigating the key taxa and their role in the environment. According to the results of our studies, these LAB isolates provide a lot of potential for use in the future, as a source of probiotics for human, animals, and starter cultures for food applications.